The critical strain - A crossover from stochastic activation to percolation of flow units during stress relaxation in metallic glass. (June 2017) - Wu, Y.C.; Wang, B.; Hu, Y.C.; Lu, Z.; Li, Y.Z.; Shang, B.S.; Wang, W.H.; Bai, H.Y.; Guan, P.F.
Abstract: The stress relaxation processes of strained Zr50 Cu50 metallic glass (MG) are investigated by molecular dynamics simulations. We provide the direct evidence for the strain-accelerated relaxation which can be attributed to the activation of flow units in MGs. Moreover, a crossover from stochastic activation to percolation of flow units corresponding to a critical applied strain can be observed. The temperature influence on the strain-accelerated dynamics is also discussed. Our results may be helpful for the understanding of the relaxation dynamics under applied strain field and deepen the comprehension of the nature of MG. Graphical abstract: